2021
DOI: 10.1093/ofid/ofab285
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bundled Interventions for Patients With Opioid Use Disorder Experiencing Homelessness Receiving Extended Antibiotics for Severe Infection

Abstract: Hospitalizations for serious infections in patients with opioid use disorder (OUD) experiencing homelessness are common. Patients receiving 4 interventions [infectious disease consultation, addiction consultation, case management, and medications for OUD (MOUD)], had higher odds of clinical cure (unadjusted OR 3.15, p= 0.03; adjusted OR 3.03, p=0.049) and successful retention in addiction care at 30 days (unadjusted OR 5.46, p=0.01; adjusted OR 6.36, p=0.003).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Our study found a similar level of overall OPAT completion (64%) as other studies of similar populations at skilled nursing facilities or SUD treatment facilities (49-73%). 6 , 13 15 Rates of OPAT completion may be lower in PWID or those experiencing homelessness, 16 which was common in our study.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Our study found a similar level of overall OPAT completion (64%) as other studies of similar populations at skilled nursing facilities or SUD treatment facilities (49-73%). 6 , 13 15 Rates of OPAT completion may be lower in PWID or those experiencing homelessness, 16 which was common in our study.…”
Section: Discussionmentioning
confidence: 64%
“…Beieler et al 13 performed a small but innovative study of four different interventions (ID consultation, addiction consultation, case management, and MOUD at discharge) in people with OUD experiencing homelessness who were treated with mostly (86%) IV antibiotics at a residential SUD treatment facility. The investigators found that use of all four interventions was associated with improved clinical cure of infection and retention in addiction treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beieler et al performed a retrospective cohort review of a bundle intervention ([1] ID consult, [2] addiction medicine consult, [3] referral to case management, and [4] medications for OUD usage [MOUD]) approach to the management of patients experiencing homelessness who require at least 14 days of antibiotic treatment (IV or oral) within a 2-year period at 1 urban county hospital in the United States [ 6 ]. In total, 53 patients were included, representing 63 infectious episodes.…”
Section: Publication Summariesmentioning
confidence: 99%
“…A growing body of evidence suggests that hospital outcomes for infectious complications of IDU are improved when people who inject opioids are treated with medications for opioid use disorder (MOUD) (8)(9)(10)(11). In patients presenting with OUD, MOUD have been associated with a decrease in all-cause mortality, overdose events, and need for acute care related to opioid use (12,13).…”
Section: Introductionmentioning
confidence: 99%